Effect of Menopause on Periodontium - Is There A Link? - Dabhi, Ruzuta Khushal Bhai; Mathur, Aditi; Shetty, Neema; Makhijani, Barkha; Manohar, Balaji; Bali, Ashish (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Menopause is associated with important systemic and oral changes. Many researchers have tried to evaluate the influence of hormonal changes associated with menopause in the periodontium, however results are still contradictory. Objective: The aim of the present study was to evaluate the effect of menopause on the severity of periodontal destruction. Methods: In the present study 25 systemically healthy women age ranges from 30 to 65 with generalised chronic periodontitis were included. They were divided into 2 groups based on their menstrual history. Group I (control group) included 8 women with normal menstrual cycle and Group II (test group) included 17 postmenopausal women. Clinical parameters Plaque Index, Gingival Index, periodontal probing pocket depth (PPD) and DMFT Index was recorded. The level of bone present was evaluated radiographically. Results: There were no significant differences between subjects of both the control and test groups in the percentages of sites for presence of plaque (p > 0.37), gingival index (p > 0.161) and DMFT index (p > 0.099). However deeper pockets (p < 0.001) and reduced bone support (p < 0.00) was observed in Group II as compared to Group I. Conclusion: The findings of the present study suggest, that postmenopausal women have more severe periodontal destruction as compared to premenopausal women.